Assistive Technologies in Smart Cities - Rafael Garcia Ramirez, Alejandro; Gitirana Gomes Ferreira, Marcelo (IntechOpen, 2018)
Cities are the places where the greatest technological advances will take place in the near future, and important efforts are being directed towards autonomy and independence for each and every citizen. However, these efforts are rarely coordinated or integrated among governments, citizens, and private firms. In this book, assistive technology solutions are approached considering the smart cities scenario. The book discusses how assistive technologies can be adapted to this new reality. In fact, several challenges arise, stimulating the evolution of current technologies, relying on ubiquitous sensing, big data, and anytime/anywhere access and control. The book presents research under development, not necessarily with consolidated results. Even though the idea of smart cities is still not a recognized concept in most countries, its relevance and application are spreading rapidly.